PENGARUH KEMAMPUAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) PUTUSSIBAU KABUPATEN KAPUAS HULU - B11109136, SURYA ADMOJO (Jurnal Manajemen Update, 2015)
This Research is done with an eye to as follows: Testing and analyzeÂ  ability influence to officer performance at company of Drinking Water Area (PDAM) Putussibau of Regency of Kapuas Hulu and test and analyze the influence motivate the job to officer performance at company of Drinking Water Area (PDAM) Putussibau of Regency of Kapuas Hulu Research use the quantitative analysis method because research data in the form of number and analyze to use the statistic. Sample of taken as in this research is the overall of jobholder amounting to 94 people. Technique analyze the used by is doubled regrets Result of research express that ability variable with the indicator by partial do] not have an effect on the significant to performance of officer of Company of Area of Drinking Water of Putussibau of Regency of Kapuas HuluÂ  and variable motivate the job by partial do not have an effect on the significant to performance of officer of Company of Area of Drinking Water of Putussibau of Regency of Kapuas Hulu Keyword : ability, motivate the job, performance